Ivory Inn Room Reservation System - Khairil Azmi, Nur Fatihah; Mohamed, Rozlini (Applied Information Technology And Computer Science, 2025)
The Ivory Inn Room Reservation is undergoing a paradigm shift towards seamless online experiences in an era marked by digital transformation. Traditional reservation methods often lack efficiency, leading to customer dissatisfaction and operational challenges for hoteliers. The online accommodation reservation system is designed to be intuitive and responsive, allowing users to navigate and make reservations across multiple devices. The hotel's online room reservation system is developed on the windows platform. During testing, a connection with an external facility was successfully established, allowing users to interact in real time. The development of online accommodation reservations will significantly reduce the time and effort required to make accommodation reservations and is expected to improve customer satisfaction.